Craniolateral acetabular denervation in dogs with hip dysplasia: to associate or not with pectineal tenectomy, iliopsoas tenotomy and ventral denervation? - Rocha, Leandro Branco; Tudury, Eduardo Alberto; de Menezes, Aline Rocha; de Sá, Marina Andrade Rangel [UNESP]; Farias, Priscilla Silva; Rolemberg, Kahena Morais; Ruschel, Marina Luísa; Santos, Edclécia de Jesus; Santos, Mariana Tibúrcio; de Oliveira, Lyana Brasil Gomes; Melo, Gustavo Almeida; Resende, Camilla Gentil; et al. (Medicina Veterinaria (UFRPE), 2021)
This study aimed to evaluate pain relief in 20 dogs with hip dysplasia that underwent pectin tenectomy and iliopsoas muscle tenotomy, associated with lateral and ventral denervations in the left antimere in comparison with the lateral denervation in the right antimere. Muscle mass gain and gait were evaluated. Specific physical examination, such as hip abduction, rotation, and extension, and iliopsoas test were performed. In both groups, joint mobility improvement and muscle mass gain were significant 60 days post-surgery. Young dogs did not show significant difference in limb mass gain when left (3.79 cm) and right (3.6 cm) limbs were compared. By contrast, adult dogs demonstrated significant difference in mass gain between the limbs, gaining 0.55 cm in the right and 1.13 cm in the left. On physical examination and specific joint evaluation, pain relief was observed in both joints 7 days post-surgery; pain was decreasing gradually until 60 days post-surgery when the difference between the left (1.61) and the right (1.55) limbs was not significant. This finding suggests that craniolateral denervation alone is sufficient to achieve good pain relief in dogs with hip dysplasia.
Desnervação acetabular crânio lateral em cães com displasia coxofemoral: associar ou não com tenectomia pectínea, tenotomia do iliopsoas e desnervação ventral?
Keywords: Canine; Dysplastic; Pain; Surgery